Ocular surface squamous neoplasia masquerades: Clinical profile and outcome - Shirali Gokharu; Deepanjali Arya; Deepender Chauhan; Sima Das (Indian Journal of Ophthalmology)
Purpose: The diagnosis of ocular surface squamous neoplasia (OSSN) is primarily clinical, confirmed through histopathology, cytology, or imaging. This study describes a series of OSSN patients with atypical clinical presentation masquerading non-neoplastic etiologies, identifies clinical features distinguishing OSSN from benign lesions, and thus aids clinicians in early diagnosis and prompt management. Methods: A retrospective review was conducted on medical records of OSSN patients, and patients initially diagnosed with anterior segment infection or inflammation were identified. Data collected included clinical presentation, initial diagnosis and treatment, response to treatment, final diagnosis, treatment type and outcome, and clinical clues to the diagnosis. Results: In the study period, 153 OSSN patients were identified from medical records of which 11 patients (7.2%) were initially diagnosed as anterior segment infection or inflammation. One patient presented with limbal stem cell deficiency, two with nodular episcleritis and necrotizing scleritis, and eight with various corneal involvement such as dendritic ulcer, corneal degeneration/dystrophy, corneal dermoid, exposure keratopathy, peripheral ulcerative keratitis, and perforated corneal ulcer. Three underwent extended enucleation due to intraocular spread, two required excision biopsies with adjuvant topical therapy, and the remaining patients were treated with topical therapy (Interferon α-2b 1% and/or mitomycin-C 0.04%). One patient was lost to follow up, one had a recurrence, and nine achieved complete resolution at mean follow-up of 18 months. Conclusion: OSSN can mimic ocular surface infection, inflammation, or degeneration. A meticulous anterior segment evaluation can provide clinical clues to diagnosis which can be confirmed on histopathology.